Molecular dynamics study of a covalent organic framework as highly-efficient and biocompatible carriers for doxorubicin delivery: the role of nanopores. (6th December 2021) - Yu, Jingping; Jia, Xiao; Yang, Yanmei; Zhang, Chao; Liu, Yang; Gao, Da; Fan, Yingcai; Li, Weifeng
Abstract: The development of highly-efficient loading, targeted delivery and controlled-release of drug carrier systems is of great significance in tumor treatment. Although various kinds of nano-carriers have been widely studied as potential anticancer delivery materials, the major concern of cytotoxicity is still an important issue before real medical applications. This is due to the strong interactions between nano-structure carriers and biomacromolecules. Herein, a covalent organic framework (COF), triazine triphenyl imine (TTI), is proposed as a promising candidate for efficient delivery and release of the anti-cancer drug, doxorubicin (DOX), by using molecular dynamics simulations. Our results demonstrated that despite there being huge pores in TTI, enough contact sites can be provided to attract the drug by π – π interactions between the anthracene rings of DOX and the framework of TTI. The loading capacity of DOX on the TTI monolayer even reach 743% because the nanopores exclude some invalid adsorption sites that exist in other 2D nano-carriers. Interestingly, the DOX molecules can not only spontaneously adsorb on the surface of the TTI monolayer in natural conditions, but also effectively release from the TTI carrier under acidic pH level. For the TTI multilayers, similar loading capacity had also been achieved due to the pore walls also playing a key role in adsorbing the DOX molecules. Moreover, by simulating a model protein interacting with TTI, mild biocompatibility of TTI monolayer and multilayer could also be achieved due to the periodic nanopores limiting the excessive adsorption with the protein that could maintain the native structure. Our results highlight the essential roles of the patterned nano-porous structure in the TTI sheets for both efficient DOX loading and release, with high biocompatibility, and provides valuable insight into COF-based nano-carriers in potential drug delivery applications.